Role of transformational leadership mediation: effect of emotional and communication intelligence towards teamwork effectiveness - Suwandana, I Gusti Made (International research journal of management, IT and social sciences, 2019)
Tourism has become a driving factor for the economy in various countries in the world. Regions that become tourist destinations have a great chance of growing supporting facilities such as the provision of accommodation, restaurants and transportation services. Bali has long been an attraction for both local and foreign tourists to visit. A large number of tourists visiting Bali has added opportunities for the tourism industry in providing accommodation services and facilities for tourists. This research was conducted to find out that transformational leadership mediates on the influence of emotional intelligence and communication on the effectiveness of the teamwork. The results show that emotional intelligence has a positive and significant effect on transformational leadership. Communication has a positive and significant effect on transformational leadership. Emotional intelligence has a positive and significant effect on team effectiveness. Communication has a positive and significant effect on team effectiveness. Transformational leadership has a positive and significant effect on team effectiveness. Transformational leadership is able to mediate the influence of emotional intelligence on team effectiveness. Transformational. Transformational leadership is able to mediate the influence of communication on team effectiveness.